Automated, machine learning‐based, 3D echocardiographic quantification of left ventricular mass. Issue 2 (28th December 2018) - Volpato, Valentina; Mor‐Avi, Victor; Narang, Akhil; Prater, David; Gonçalves, Alexandra; Tamborini, Gloria; Fusini, Laura; Pepi, Mauro; Patel, Amit R.; Lang, Roberto M.
Abstract : Background: Although 3D echocardiography (3DE) circumvents many limitations of 2D echocardiography by allowing direct measurements of left ventricular (LV) mass, it is seldom used in clinical practice due to time‐consuming analysis. A recently developed 3DE machine learning (ML) approach allows automated determination of LV mass. We aimed to evaluate the accuracy of this new approach by comparing it to cardiac magnetic resonance (CMR) reference and to conventional 3DE volumetric analysis. Methods: We prospectively studied 23 patients who underwent 3DE (Philips EPIQ) and CMR imaging on the same day. Single‐beat wide‐angle 3D datasets of the left ventricle were acquired. LV mass was quantified using the new automated software (Philips HeartModel) with manual corrections when necessary and using conventional volumetric analysis (TomTec). CMR analysis was performed by manual slice‐by‐slice tracing of LV endo‐ and epicardial boundaries. Reproducibility of the ML approach was assessed using repeated measurements and quantified by intra‐class correlation (ICC) and coefficients of variation (CoV). Results: Automated LV mass measurements were feasible in 20 patients (87%). The results were similar to CMR‐derived values (Bland‐Altman bias 5 g, limits of agreement ±37 g) and also to the conventional 3DE analysis (bias 7 g, ±27 g). Processing time was considerably shorter: 1.02 ± 0.24 minutes (CMR: 2.20 ± 0.13 minutes; TomTec: 2.36 ± 0.09 minutes), although manual corrections were performed in most patients. Repeated measurements showed high reproducibility: ICC = 0.99; CoV = 4 ± 5%. Conclusions: 3D Echocardiography analysis of LV mass using novel ML‐based algorithm is feasible, fast, and accurate and may thus facilitate the incorporation of 3DE measurements of LV mass into clinical practice.